The Relationship Between Education and Social Value in The Novel “The Magician’s Apprentice” By: Trudi Canavan - Rohdearni Wati Sipayung (Budapest International Research and Critics University, 2018)
This novel has many basic values of human, and the writer wants to share about the social value of this Novel. Although this novel tells of a witch, as we know that the stories of about witches, it may be difficult to find which part is the social value. But the writer wants to find the part that is a social value, because in every story there must be a positive value that can be taken by the reader. The social value of Cooperation, cooperation within a group can make the job easier. The social value of care. Human beings we should care about each other, helping each other and pay attention. The social value of bravery, in life we must have the courage because, as we know there are still many people who are afraid to face the people.